2020
DOI: 10.1111/apa.15526
|View full text |Cite
|
Sign up to set email alerts
|

A narrative review with practical advice on how to decrease pain and distress during venepuncture and peripheral intravenous cannulation

Abstract: Venepuncture and peripheral intravenous cannulation are two of the most commonly paediatric performed medical procedures in many healthcare settings. These procedures can cause significant pain and distress at any age, during childhood, so appropriate management is strongly recommended. This review examines the evidence related to pain and distress management during venepuncture and peripheral intravenous cannulation, including preparing the environment, assessing and preparing patients, parental involvement a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 61 publications
(106 reference statements)
0
12
0
Order By: Relevance
“…Needle-related procedures are the most common sources of distress and pain in paediatric Eds [2]. While the concern for understanding and management of the unpleasant sensory and emotional experience associated with painful medical procedures in children has increased in past years [4,8], limited data is available for adolescents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Needle-related procedures are the most common sources of distress and pain in paediatric Eds [2]. While the concern for understanding and management of the unpleasant sensory and emotional experience associated with painful medical procedures in children has increased in past years [4,8], limited data is available for adolescents.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, an awareness of the impact on needle procedures in the EDs may be relevant in order to develop strategies to limit needle phobia in adults and its related consequences and costs. Topical and local anaesthesia through the application of anaesthetic creams or injecting buffered lidocaine is the most effective pain relief technique during peripheral intravenous cannulation [2,15]. Nevertheless, a recent survey focused on European paediatric EDs showed that their availability and use is still limited [19].…”
Section: Discussionmentioning
confidence: 99%
“…are commonly adopted clinically to relieve pain in patients. However, opioids may still cause adverse reactions such as nausea, vomiting, respiratory depression and hallucination for patients, even though its dose has been reduced [ [7] , [8] , [9] ]. Therefore, non-drug therapies, such as music therapy, cognitive behavioral therapy and animal assisted therapy (AAT), are preferred by healthcare staff and patients due to their minimal side effects and easy implementation.…”
Section: Introductionmentioning
confidence: 99%
“…Intravenous (IV) cannulation is an invasive procedure that provokes stress, pain, anxiety, and fear in patients [ 1 , 2 , 3 , 4 ]. These unpleasant feelings can have adverse implications for future treatment and care of patients, so appropriate pain and anxiety management is of paramount importance [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…These unpleasant feelings can have adverse implications for future treatment and care of patients, so appropriate pain and anxiety management is of paramount importance [ 5 , 6 ]. Pharmacological and nonpharmacological interventions to reduce the pain and anxiety associated with peripheral IV cannulation (PIC) have been described [ 1 , 7 , 8 ]. Although local anesthesia injection, local anesthetic cream, and vapocoolant spray are widely reported to reduce pain during PIC [ 9 , 10 , 11 ], these strategies target pain but do not address anxiety and fear.…”
Section: Introductionmentioning
confidence: 99%